Innovation Management Processes and Routines for Business Success and Value Creation - Vala, Luís (2019)
Innovation is managed through the development of processes and routines, considered as critical for business success and value creation. The identification of relevant routines as well as the understanding of which factors affect business innovation is the main objective of this research, based on a survey applied in Portuguese companies and their experience shared in best practices guides. Conclusions highlighted 10 key innovation routines, reinforcing the idea that innovation must be supported through a systematic and sustained management process. Results also indicate that SMEs face greater difficulties in benefiting from the potential of innovation practices and collaboration may present opportunities to overcome their limited resources. Therefore, regardless of size, business activity, science and technology intensity or other factors influencing firms dynamic capabilities, innovation should be considered as a management imperative as it can influence not only the present but also the future of business success.